Pengaruh Sistem Informasi Akuntansi dan Sistem Pengendalian Intern terhadap Kualitas Laporan Keuangan dengan Good Corporate Governance sebagai Variabel Moderasi (Studi Kasus Eyelink Group) - Berliana Nur Maulida; Tumirin Tumirin (Jurnal Riset Akuntansi, 2025)
This study aims to examine the influence of Accounting Information Systems (AIS) and Internal Control Systems (ICS) on the quality of financial statements, with Good Corporate Governance (GCG) as a moderating variable. This quantitative research employs Partial Least Squares (PLS) analysis on 36 respondents from Eyelink Group. The results indicate that AIS and ICS do not significantly affect the quality of financial statements. However, GCG has a significant effect on the quality of financial statements and strengthens the relationship between AIS and financial statement quality. GCG does not show significant moderation in the relationship between ICS and financial statement quality. This study highlights the importance of implementing effective GCG to improve financial statement quality and support optimal AIS implementation.